Effects of anodic transcranial direct current stimulation combined with physical training on the performance of elite swimmers - Yang, Xipeng; Wu, Jinlong; Tang, Yucheng; Ren, Zhanbing (Frontiers in Physiology, 2024)
The manuscript presents Anode transcranial direct current stimulation, which was used to verify whether the method was effective in improving the athletic performance of swimmers. Further, We believe that this paper will be of interest to your journal readers as we introduce that anodic transcranial direct current stimulation is a non-invasive technique that can be used in swimmers' daily training to improve athletic performance, in line with the thematic scope of Frontiers in Psychology in sports science. We believe that our study makes a significant contribution to the literature Because we solve the gap of whether anodic transcranial direct current technology can improve the athletic performance of swimmers. I appreciate your consideration. I am looking forward to hearing from you.